Nepal Development Update, April 2021 : Harnessing Export Potential for a Green, Inclusive, and Resilient Recovery - World Bank Group (World Bank, Kathmandu, 2021)
Nepal has been hit hard by COVID-19, although the situation has improved more recently. As the outbreak became widespread in mid-2020, a nationwide lockdown was implemented from March to July in 2020, followed by localized lockdowns, including in the Kathmandu Valley up until mid-September. During this time transportation, education and tourism-related activities were significantly restricted. Since October, the number of cases has been declining steadily, allowing a gradual easing of movement restrictions. Nepal launched its vaccination program on January 27, 2021, and about 5.9 percent of the population (or 1,791,606 people) were inoculated by mid-March 2021. Thus, there are good prospects that further outbreaks of COVID-19 can be contained. After contracting for the first time in 40 years in FY20 - by 1.9 percent - the economy showed signs of moderate recovery in the first half of FY21. Activity resumed in wholesale and retail trade, transport, and financial services, while favorable monsoons drove robust agricultural growth. However, tourism remained at a standstill and private investment anemic given high levels of overall uncertainty related to the epidemic as well as political developments. Uncertainty arising from the epidemic has also contributed to fiscal risks due to the degree of fiscal stimulus provided to support individuals and firms and which will need to eventually be rolled back for fiscal sustainability. Political uncertainty also heightened in December 2020 when the Prime Minister dissolved Parliament. The Supreme Court overturned the decision, reinstating Parliament in February 2021 and precipitating the split of the two-party majority coalition in March.